Effect of pH and salt concentration on protein solubility of slaughtered and non-slaughtered broiler chicken meat - Mst Kamrun Nahar,; Zarina Zakaria,; Uda Hashim,; Md Fazlul Bari, (Penerbit Universiti Kebangsaan Malaysia, 2017)
This study examined the influence of pH and salt concentration on the protein solubility of slaughtered and non-slaughtered broiler chicken meat. Three types of salt (NaCl, Na2SO4, and (NH4)2SO4), five different pH levels (5.0, 6.0, 7.0, 8.0 and 9.0) and five salt concentrations (0.4, 0.8, 1.2, 1.6, and 2.0 M) were examined. Each type of salt showed distinctive activities for slaughtered and non-slaughtered meat protein solubility. Soluble protein concentration increased as pH increased (p<0.05) from pH5.0 to 8.0 and decreased from pH8.0 to 9.0. It was also observed that protein solubility increased as the salt concentration increased. Protein solubility significantly increased (p<0.05) in the non-slaughtered meat compared to the slaughtered meat at pH8.0 for Na2SO4 at 1.2 M.